Caution in diagnosing angioedema as anaphylaxis. Issue 9 (4th September 2019) - Patel, Shivam; Mathew, Roshan; Bhoi, Sanjeev
Abstract : Angioedema is one of the commonest life-threatening conditions with good outcome timely definitive treatment. However, failure to recognise the common presentation of an uncommon bradykinin-mediated angioedema in time may lead to fatal outcome in the emergency department (ED). We report a case of a 79-year-old male patient who presented to ED with features of ACE inhibitor-induced angioedema which was identified and resuscitated by the emergency physician with use of fresh frozen plasma (FFP) leading to prompt recovery and good outcome.